2015
DOI: 10.5152/turkpediatriars.2015.3164
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body ingestion in children

Abstract: Aim: Foreign bodies ingested by the oral route enter into the gastrointestinal tract and are considered a significant health problem in the childhood. In this study, we evaluated the pediatric patients who presented to our hospital with the complaint of ingestion of foreign body. Material and Methods:The hospital records of all children who presented to our clinic because of ingestion of foreign body between January 2008 and January 2015 were examined retrospectively. The complaints at admission, the types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
61
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 21 publications
9
61
2
3
Order By: Relevance
“…Dereci et al and Çevik et al [9,12] reported that the most frequent localization was the upper esophagus. Vukovic et al [13] reported that foreign bodies were seen in the distal esophagus at a rate of 87%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dereci et al and Çevik et al [9,12] reported that the most frequent localization was the upper esophagus. Vukovic et al [13] reported that foreign bodies were seen in the distal esophagus at a rate of 87%.…”
Section: Discussionmentioning
confidence: 98%
“…[12] Vukovic et al [13] reported frequent use of urgent endoscopy due to FBI at a rate of 67.9%; however, they acknowledged that it is often unnecessary, and that observation and follow-up is typically the best approach, with the exception of long objects or objects with sharp edges. Denney et al [8] found that foreign body localization occurred most frequently in the upper esophagus and reported a success rate of 99% with endoscopic removal.…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs in patients between 6 months and 5 years of age 8 . Although most of the ingested objects passing through the stomach are expelled without injury 9,10 , 20% are trapped at the anatomical narrowings of the esophagus, pylorus, or ileocecal valve 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs in patients between 6 months and 5 years of age 8 . Although most of the ingested objects passing through the stomach are expelled without injury 9,10 , 20% are trapped at the anatomical narrowings of the esophagus, pylorus, or ileocecal valve 8 . Only 10-20% of patients who ingest foreign bodies will require endoscopic extraction 11 and about 1% surgical intervention due to complications such as fistulae 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] More commitment and dedication is needed to ensure adequate prevention by caregivers, which requires parent educational programs in order to prevent habits that predispose to accidents. Prevention is a key element in reducing the morbidity and mortality associated with these cases.…”
mentioning
confidence: 99%